A Cysteine‐Mediated Synthesis of Red Phosphorus Nanosheets. (20th April 2021) - Mo, Jianbin; Xu, Yun; Zhu, Longqian; Wei, Wei; Zhao, Jing
Abstract: Among phosphorus‐based nanomaterials, layered black phosphorus and violet phosphorus have been actively explored in the past decade. However, methods for the synthesis of red phosphorus nanosheets (RPNSs) is lacking, even though red phosphorus (RP) is commercially available at low cost and has excellent chemical stability at room temperature. We report an efficient strategy for fabrication of RPNSs and doped RPNSs using cysteine as a reducing reagent. Data from in vitro and in vivo studies suggested that RPNSs can trigger production of reactive oxygen species, DNA damage, and subsequent autophagy‐mediated cell death in a shape‐dependent manner. Our findings provide a method for construction of layered RP nanomaterials and they present a unique mechanism for the application of phosphorus‐based materials in nanomedicines. Abstract : A redox method was developed for fabrication of red phosphorus nanosheets (RPNSs). Cysteine was responsible for assembly of the RPNSs, and the addition of acetylacetonate enabled the construction of doped RPNSs. In vitro and in vivo results confirmed that native RPNSs induce drastic autophagy in tumor chemotherapy.